Visualising variation in mortality rates across the life course and by sex, USA and comparator states, 1933–2010. Issue 8 (1st March 2016) - Vanderbloemen, Laura; Dorling, Danny; Minton, Jonathan
Abstract : Background: Previous research showed that younger adult males in the USA have, since the 1950s, died at a faster rate than females of the same age. In this paper, we quantify this difference, and explore possible explanations for the differences at different ages and in different years. Methods: Using data from the Human Mortality Database (HMD), the number of additional male deaths per 10 000 female deaths was calculated for each year from 1933 to 2010, and for each year of age from 0 to 60 years, for the USA, and a number of other countries for comparison. The data were explored visually using shaded contour plots. Results: Gender differences in excess mortality have increased. Coming of age (between the ages of 15 and 25 years of age) is especially perilous for men relative to women now compared with the past in the USA; the visualisations highlight this change as important. Conclusions: Sex differences in mortality risks at various ages are not static. While women may today have an advantage when it comes to life expectancy, in the USA, this has greatly increased since the 1930s. Just as young adulthood for women has been made safer through safer antenatal and childbirth practices, changes in public policy can make the social environment safer for men.